2020
DOI: 10.1530/rep-20-0202
|View full text |Cite
|
Sign up to set email alerts
|

YAP and TAZ are required for the postnatal development and the maintenance of the structural integrity of the oviduct

Abstract: The development of the Müllerian ducts into the female reproductive tract requires the coordination of multiple signaling pathways that regulate proliferation, apoptosis and differentiation. The Hippo pathway has been reported to interact with several pathways with established roles in Müllerian duct development; yet, its potential roles in reproductive tract development and function remain mostly uncharacterized. The objective of this study was therefore to characterize the roles of the Hippo transcriptional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 47 publications
1
10
2
Order By: Relevance
“…During the earliest stages of embryogenesis, loss of either gene individually does not cause a pre-implantation defect; however, dual knockout (KO) Yap1 −/− ;Wwtr1 −/− embryos die before the 32 cell stage, implying that they are essential but redundant for morula formation [30]. While more sophisticated conditional KOs have shown that Yap1 plays critical roles in the cranial neural crest, female reproductive tract, and heart valves, these phenotypes tended to be late or post-natal, and it would be fruitful to apply conditional KO in the early embryo or placenta to revisit the null phenotypes [31][32][33].…”
Section: Phenotypes Of Yap1 Insufficiency In the Mouse Embryomentioning
confidence: 99%
See 2 more Smart Citations
“…During the earliest stages of embryogenesis, loss of either gene individually does not cause a pre-implantation defect; however, dual knockout (KO) Yap1 −/− ;Wwtr1 −/− embryos die before the 32 cell stage, implying that they are essential but redundant for morula formation [30]. While more sophisticated conditional KOs have shown that Yap1 plays critical roles in the cranial neural crest, female reproductive tract, and heart valves, these phenotypes tended to be late or post-natal, and it would be fruitful to apply conditional KO in the early embryo or placenta to revisit the null phenotypes [31][32][33].…”
Section: Phenotypes Of Yap1 Insufficiency In the Mouse Embryomentioning
confidence: 99%
“…As paralogs with high (~ 50%) sequence identity, these two proteins possess both redundant (i.e., they can genetically compensate for one another) and non-redundant roles [2]. They have a similar target gene profile, and they are redundant in the oviduct, heart, urinary tract, and other organs [31,[103][104][105]. However, they have numerous context-specific differences and fulfill distinct roles during embryogenesis and cell fate specification.…”
Section: Differences In Protein Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The hippo pathway is a critical regulator of morphogenesis, organ size determination, and tumourigenesis in many tissues, including the reproductive system [10][11][12]. Formation of the YAP/TAZ-TEADs complex serves as the key mechanism that stimulates the expression of target genes (e.g., connective tissue growth factor and cysteine-rich angiogenic inducer 61) that are essential for cell proliferation and survival [13].…”
Section: Introductionmentioning
confidence: 99%
“…This is a very complex process. In the reproductive system, including the oviduct, angiogenesis is modulated by angiogenic/growth factors [7,8,10], anti-angiogenic factors [11][12][13], reproductive hormones [14,15], eicosanoids [9,16], nitric oxide [16,17], tumor necrosis factor α (TNFα) [18], oxygen (O 2 ) content [19,20], and other factors [21][22][23]. Among a plethora of angiogenic/growth factors are vascular endothelial growth factor (VEGF) and its receptors 1 (VEGFR1) and 2 (VEGFR2, also known as kinase insert domain receptor-KDR) and fibroblast growth factor 1 and 2 (FGF1 and FGF2) and their receptors FGFR1 and FGFR2 [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%